Professional construction management including C.M., design-construct, and general contracting - Barrie, Donald S. (McGraw-Hill series in construction engineering and management, 1992)
The subjects covered in this book include those normally studied in an introductory overview course on construction management, and there is enough depth and added material to serve as the basis for a more advanced course, focusing on organizational and contractual approaches to project management, and the related planning and control systems. This new edition strengthens its coverage of the business aspects of the industry, with a section devoted solely to the business methods in professional construction management. The text's practical in-depth approach to the major engineering and management techniques appeals to both students and practitioners alike.